THE LARYNGECTOMY PATIENT’S VIEW OF SOCIAL WORK SUPPORT SERVICES IN A HOSPITAL SETTING - Steyn, Henriëtte; Green, Sulina (Social Work/Maatskaplike Werk, 2010)
A laryngectomy is a surgical procedure entailing the removal of the entire larynx following a diagnosis of an advanced stage or recurrence of cancer of the larynx or hypopharynx (Casper & Colton, 1998:1; Silver & Ferlito, 1996:179; Stell, 1991:212). Severe smoking and alcohol use, especially in combination, can be seen as major risk factors for cancer of the head and neck area, including larynx cancer (Byrne, Walsh, Farrelly & O’Driscoll, 1993:174; Depondt & Gehanno, 1995:33; Doyle, 1994:17; Stam, Koopmans & Mathieson, 1991:44; Terrell, Ronis, Fowler, Bradford, Chepeha, Prince, Teknos, Wolf & Duffy, 2004:402). People at greatest risk of contracting larynx cancer appear to be male smokers between the ages of 45 and 75 years (Ross, 2000:13). The disease usually occurs in late middle age (retirement) and can therefore be seen as a disease of the elderly (Belch & Beamish, 1992:61; Deshmane, Parikh, Pinni, Parikh & Rao, 1995:121; Frith, Buffalo & Montague, 1985:476; Renner, 1995:216; Ross, 2000:14). This pattern is undergoing change, however, as an increasing number of women and younger persons are presently being diagnosed with cancer of the larynx (Belch & Beamish, 1992:61; Eadie & Doyle, 2005:122; Renner, 1995:216; Ross, 2000:13; Smithwick, Davis, Dancer, Hicks & Montague, 2002:206), mainly as a result of increased tobacco consumption or changes in smoking and drinking behaviour (Dhooper, 1985:217; Doyle, 1994:16; Smithwick et al., 2002:206)